Two-Phase Flow Measuring with Ultrasonic Tomography - QORBANI, Omid; AGHDAM, Esmaeil Najafi (Archives of Acoustics, 2020)
The exact measurement of multiphase flow is an important and essential task in the oil and petrochemical related industries. Several methods have already been proposed in this field. In the existing methods, flow rate measurement depends on the fluid flow pattern. Flow pattern recognition requiring calibration has created instability in such systems. In this paper, a imple and reliable method is proposed which is based on ultrasonic tomography. It is free from calibration and instability problems that existing methods have. The obtained data from a 32-digit array of ultrasonic sensors have been used and the two-phase flow rate including liquid and gas phases have been calculated through a simple algebraic algorithm. Simulation results show that while applying this method the measurement technique is independent from the fluid flow pattern and the system error is decreased. For the proposed algorithm, the average amount of the spatial imaging error (SIE) for a bubble at different positions inside the pipe is about 5%.